Familial Aquagenic Urticaria - Vieira, Beatriz dos Santos (2021)
Aquagenic urticaria (AU) is a rare form of physical urticaria precipitated by water contact with the skin, whatever their temperature and nature. The pathophysiology is not yet quite clear. There are fewer than 50 cases reported. Most cases are sporadic but there are a small number of familial cases. We report a case of familial AU in two children (brother and sister). To the best of our knowledge, no case of familial AU has been reported in Portugal. With this two related cases, the authors wish to emphasize that although this is a type of physical urticaria rare in children, it should be recognized because can cause systemic potentially fatal reactions and an adequate treatment can allow a better quality of life.